Policy content meaningfulness of school leaders in Malaysia: Exploratory factor analysis. International Conference on Asean and Globalisation - Noryati, Alias; Zainudin, Awang; Habsah, Muda (2018)
The purpose of this study is to develop a scale for assessing the policy content meaningfulness among school leaders in Malaysia. An exploratory factor analysis (EFA) revealed that the 3 components of the policy content meaningfulness construct; namely the personal meaningfulness, client meaningfulness and societal meaningfulness were maintained. Fur thermore, the reliability analysis was also examined via the Cronbach alpha coefficient for all extracted components for the reason in ensuring the internal consistency of the scale. This study shall add up value to the current level of knowledge in the ex isting literature of policy content meaningfulness and commands some implications to the policy makers as well.